The 'Rush Hour' of Life: Insecurities and Strains in Early Life Phases as a Challenge for a Life Course-Oriented, Sustainable Social Policy - Ute Klammer (Intergenerational Justice Review)
Empirical data proves that, in Germany, the majority of flexibility risks in the labour market (such as fixed-time contracts, temp work, unemployment etc.) are taken by the young generation and by unskilled workers. If uncertain labour market attachment occurs in the stage of family planning, the resulting insecurity and uncertainty can lead to special challenges where professional and private demands have to be reconciled (the ‘rush hour’ of life). The extent to which precarious employments and other labour market risks in early life phases affect the people concerned in the long run can only be determined by looking at entire biographies, in particular at life and labour courses. This article discusses relevant empirical data and describes possible approaches to tackle strains of specific work groups and life phases, in order to develop a life course oriented, sustainable social policy. This includes the support of continuous employment, but also the ‘straightening out’ of life courses by providing new possibilities to adjust money and (work) time to different life stages with differing financial and time requirements.